Learning Management of Nonformal Education Units in Sanggar Kegiatan Belajar - Sufyan, Anis; Nurhalim, Khomsun; Shofwan, Imam (Universitas Negeri Semarang, 2019)
Learning in the Semarang Nonformal Education Unit Sanggar Kegiatan Belajar (SKB) equality education especially the package C program focuses more on students or learning citizens, namely the occurrence of the learning process. The diversity of the backgrounds of the learning community makes participation in the learning process and the learning outcomes of each learning citizen more varied. In the learning process the learning climate created by tutors is more centered on learning centers. The purpose of this study is to describe and analyze Package C learning. This study uses a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation and conclusion drawing. Check the validity of the data using source triangulation and methods. The results of the study show that the learning plan of the Package C Program includes: formulating learning objectives, teaching materials, methods, learning resources and establishing assessment of learning outcomes. Implementation involves three steps, namely introduction, core and closing. The learning evaluation that is apllied is summative and formative evaluation.